PERENCANAAN GEDUNG OLAHRAGA MINI DAN GEDUNG SERBA GUNA DESA PACALAN - Febrione Putri Rakhmanty; Rully Rully; Abito Bamban Yuuwono (GANESHA: Jurnal Pengabdian Masyarakat, 2024)
Pacalan Village is one of the villages in Plaosan District, Magetan. The geographical condition of Pacalan Village is a valley area with extreme contoured land with the majority of the population are entrepreneurs and farmers. The Village Government wants to complete the public facilities that can be used by the community to accommodate their arts and sports activities by building a mini sports hall and meeting hall on village-owned land located on the north and east sides of the Pacalan Village Hall. The project scoupd is to make a design proposal for the requested facilities, starting with a survey and location analysis, analysis of space requirements, which then produces a design proposal and layout for the Mini Sports Hall and Meeting Hall. It is hoped that design will be useful as an initial reference for developing public facilities that can be used to accommodate the arts and sports activities of the Pacalan Village Community and its surroundings.